ENHANCING STUDENTS’ WRITING SKILLS THROUGH MOBILE-ASSISTED LANGUAGE LEARNING: THE USE OF CAKAP AND BUSUU APPLICATIONS - Atalisi Zalukhu; Fitria Rahmawati; Aliya Noor Cahyani; Maryam Sorohiti (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
This study investigated the effectiveness of Mobile-Assisted Language Learning (MALL) in enhancing students’ writing skills through the use of the CAKAP and Busuu applications. The objectives of the study were to examine the effect of the CAKAP application on students’ writing skills, to determine the effect of the Busuu application on students’ writing skills, and to identify which application provides a more significant improvement in students’ writing performance. The study employed a quantitative research design using a quasi-experimental method involving three classes: Experimental Class I (CAKAP), Experimental Class II (Busuu), and a control class receiving conventional instruction. Pre-tests and post-tests were administered to measure students’ writing ability before and after the treatment. The data were collected through writing tests and analyzed using a t-test. The findings revealed that students’ writing ability before the treatment was relatively low in both experimental groups. After the implementation of the applications, students in both experimental classes showed significant improvement in their writing performance. The t-test results indicated that the t-value for the CAKAP group (11.611) was higher than the t-table value (1.68657) at the significance level of 0.05 with a degree of freedom of 35. Similarly, the Busuu group showed a t-value of 11.501, which was also higher than the t-table value. These results indicate that both applications significantly improved students’ writing skills. However, the CAKAP application demonstrated a slightly higher effect compared to the Busuu application. Therefore, the alternative hypothesis was accepted, and the null hypothesis was rejected. The study suggests that mobile-assisted language learning applications such as CAKAP and Busuu can serve as effective tools for improving students’ writing skills in English language learning contexts.